Research Progress on Encapsulation of Hydrophobic Active Substances in Oil Bodies - YANG Yao, FU Rao, MEI Yaxin, ZHAO Sijia, WEN Xin, NI Yuanying, LI Mo (Shipin Kexue)
Oil bodies are organelles that store lipid in oil crops, and they are natural oil-in-water structures. As an encapsulation system for hydrophobic active substances, they can be used to address issues such as poor water solubility and instability of hydrophobic active substances, and have attracted wide attention from researchers in recent years. The cell membrane of oil bodies is composed of phospholipids and proteins. Hydrophobic active substances could enter oil bodies through passive transport, but the encapsulation effect is affected by many factors and can be improved by physical methods (such as stirring, ultrasonic treatment and homogenization). This article reviews recent progress on the encapsulation of hydrophobic active substances by oil bodies, focusing on the composition and properties of oil bodies, the properties of and delivery systems for hydrophobic active substances, the commonly used methods for oil body encapsulation along with their advantages and disadvantages, and the stability and encapsulation effect of oil body emulsions. The aim is to provide ideas for exploring the encapsulation mechanism of hydrophobic active substances and constructing an efficient and stable loading system. It also aims to improve the stability, utilization rate, and bioaccessibility of active substances in order to lay a theoretical foundation for their application in fields such as foods, medicine, and cosmetics.